Simulated environments for health education: report of a pedagogical experience - Ramos Velásquez, Martha Patricia
Health simulation is used as a training strategy that allows the appropriation of knowledge in a practical way through the use of physical, digital and interactive tools. Its purpose is given by the prevention of consequences of inadequate execution in processes carried out directly on patients, such as taking vital signs, assistance with feeding, venipuncture (cannulation, taking laboratory tests), preparation of material in the work of childbirth, patient care, neonatal adaptation, user service, quality management. The objective of this article is to present the report on a pedagogical experience that offers simulation as a pedagogical strategy for the training of personnel in the health sector according to an experience lived within the Center for the Training of Human Talent in Health (CFTHS). Methodology: a review of the scientific literature related to training was carried out through the use of simulated environments. Databases such as Scielo, Pubmed, Scopus, and Google Scholar were taken as references. Problem: How to integrate simulation into pedagogical strategies for training health personnel at CFTHS? Conclusion: simulation is an essential element in the performance of learners, which allows strengthening the development of competencies, defined as knowing how to do in context, from the humanistic proposal of knowledge, know-how and being. It is proposed that technical skills and soft skills are enhanced through practice in scenarios that include simulation.